Complex Tasks, Delegation, and Flexibility: What Role for Engagement and Shared Leadership? - Dionísio, António (2022)
Task complexity is one of the main factors studied by academics and is at the center of leaders’ concerns. It is related to delegation and flexibility, which are enhanced by workers’ engagement and depend on how leadership is shared. In this context, this research was carried out with the main objective of testing the serial mediating effect of engagement and shared leadership on the relationship between task complexity and flexibility and the elationship between task complexity and delegation. The sample for this study consists of 368 participants, all of whom work in organizations based in Portugal. The results indicate that task complexity is positively and significantly associated with engagement, shared leadership, flexibility, and delegation. Shared leadership has a positive and significant association with flexibility and delegation. The serial mediating effect of engagement and shared leadership on the relationship between task complexity and flexibility was confirmed. The serial mediating effect of engagement and shared leadership on the relationship between task complexity and delegation was not confirmed.